Evaluation of the relationship between the breeder’s age, breed and the incubator types on quality and animal welfare in the hatchery - Oro, Camila De Souza [UNESP]; De Souza, F. E.Z.; Rodrigues, W. C.; Oro, J. S.; Guirro, E. C.B.P. [UNESP] (FapUNIFESP (SciELO), 2019)
About 33.3% of chicken life is conditioned by the result of embryonic development. Therefore, understanding and improving the early phase of the broiler’s life is critical to guarantee their well-being. Thus, the objective of this research was to evaluate the relationship between the breeder’s age, breed and the incubator types on quality and animal welfare in the hatchery. The experimental design was completely randomized in a 2 × 2 × 3 factorial arrangement (incubator, breed and age), with 12 treatments and 6 replicates each. The eggs derived of Cobb 500 and Ross’s breeders at the beginning of the laying period, middle age and at the end of the laying period. It is concluded that the size of the eggs is related to the breeder’s age and breed, which influences directly the number of bled eggs. In addition, well-being in the hatchery can be affected by decreased hatching and contamination that is higher in older breeders. Cobb eggs also need more attention because they are larger, therefore, they have a higher risk of breakage and they are more sensitive to the low concentration of CO2 at the hatcher.
Keywords: Embryos; Hatch; Poultry